The Relationship of Knowledge and Attitude of Teenager with Sexuality Behavior in SMA Negeri 10 Rejang Lebong Regency - Santoso Ujang Effendi; Fikitri Marya Sari; Yogi Radinata (Jurnal Sains Kesehatan, 2019)
Teenage sexual behavior at risk will have an impact on increasing teenage pregnancy transmitted infection. The purpose of this study is to determine the Relationship of Knowledge and Attitude of Teenager with Sexuality Behavior in SMA Negeri 10 Rejang Lebong Regency.This study used analytical survey with Cross Sectional design. Population in this study were all students of class X and XI from SMA Negeri 10 Rejang Lebong Regency in academic year of 2017/2018. Sampling technique in this study used Simple Random Sampling. Collection data in this study used secondary and primary data who obtained from direct interviewedto the respondents. Data analysis technique in this study used univariate and bivariate analysis with Chi-Square test.The results of this study showed there was a significant relationship between knowledge and behavior of Teenager in SMA Negeri 10 Rejang Lebong Regency with moderate category relationship and there was no significant relationship between attitude and behavior of teenager in SMA Negeri 10 Rejang Lebong Regency.It is expected that students from SMA Negeri 10 Rejang LebongRegency will read more books and seek information about sexual health. Keywords: attitude, knowledge, sexuality behavior